A novel scattering switch-on detection technique for target-induced plasmon-coupling based sensing by single-particle optical anisotropy imaging. Issue 48 (26th May 2016) - Peng, Lan; Cao, Xuan; Xiong, Bin; He, Yan; Yeung, Edward S.
Abstract : A novel scattering switch-on detection technique by using flash-lamp polarization darkfield microscopy (FLPDM) has been proposed for target-induced plasmon-coupling based sensing in homogeneous solution. Abstract : We reported a novel scattering switch-on detection technique using flash-lamp polarization darkfield microscopy (FLPDM) for target-induced plasmon-coupling based sensing in homogeneous solution. With this method, we demonstrated sub-nM sensitivity for hydrogen sulfide (H2 S) detection over a dynamic range of five orders of magnitude. This robust technique holds great promise for applications in toxic environmental pollutants and biological molecules.